The Soviet Communist Party in Disarray - Rees, E. author. aut Link
VII, 226 p.
Keywords: This book presents an in-depth analysis of the proceedings of the XXVIII Congress of the Communist Party of the Soviet Union. It explores the struggle for power between radicals, reformers and conservatives, focusing on the debate on political reform, the role of the Party, Soviet history, economic restructuring, the nationalities question and foreign policy. It makes a contribution to the study of the history of the Soviet Communist Party, and provides insights into the ideological debate raging within the Party regarding the future of perestroika.